ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PELAYANAN KEBIDANAN DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP RSUD PANYABUNGAN TAHUN 2022 - HARAHAP, GUSLAINI PURNAMA INTAN PAN; Asriwati; Nur’aini; Wiwi Wardani Tanjung; Eva Yusnita Nasution (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Users of hospital services, namely patients, demand quality service. Patients will feel satisfied when they get quality service. Surveys conducted at Panyabungan Hospital, there were several problems found such as patients felt officers were not fast in providing action, lack of cleanliness of toilets in the room, officers sometimes not friendly to respond to patients, and officers sometimes incomplete providing information about patient complaints. This study aims to analyze the factors that affect midwifery services with patient satisfaction in the Inpatient Room of Panyabungan Hospital in 2022. The type of research used is analytical with a cross sectional design. The population in this study was all elective post-sectio inpatients at RSUD Panyabungan. The sample in this study amounted to 73 people, the sampling technique used purposive sampling techniques. Data were obtained through the results of interviews using questionnaires. The data analysis method was analyzed univariately, bivariately using the Chi-Square test at a 95% confidence level (P<0.05) and a multivariate test with multiple regression tests. The results showed that assurance, tangible, empathy, responsive variables were related to patient satisfaction at Panyabungan Hospital. The most dominant variable is assurance. It is recommended to RSUD Panyabungan to conduct periodic and continuous patient satisfaction surveys to evaluate the performance of health services and service quality at RSUD Panyabungan.